DEVELOPING HUMANISTIC COMPETENCE THROUGH INTERACTIVE METHODS IN SOCIAL NETWORKS (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the development of humanistic competence among students through interactive methods in social networks. In contemporary education, social networks have become an important space for communication, self-expression, cooperation and value formation. Students participate in online discussions, exchange opinions, respond to social issues and create digital content. These processes can support the development of empathy, tolerance, civic responsibility, ethical communication and respect for human dignity when they are guided by pedagogical goals. The thesis analyzes interactive methods such as online discussion, digital storytelling, collaborative projects, problem-based dialogue, peer feedback and reflective communication. The results show that social networks can become a meaningful educational environment if interaction is organized on the basis of humanistic values, media literacy and responsible digital behavior.
Keywords: Humanistic competence, social networks, interactive methods, digital education, empathy, tolerance, ethical communication, media literacy, civic responsibility.